Study of the Sexual Behaviors and Influential Factors Affecting Premenopausal Women with Breast Cancer: Application of the Method of Triangulation - Eun Ja Kim; Myung Ae Kim; Na Hyun Kim (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was conducted to investigate sexual behaviors and influencing factors affecting premenopausal women who have breast cancer and have undergone surgery. METHODS: Seventy premenopausal women, ranging between 35~55 years of age, were included in this study. Sexual behaviors were evaluated using the WSBQ-F (Wilmoth Sexual Behaviors Questionnaire-Female). The in-depth interview was analyzed utilizing content analysis. RESULTS: There were no significant differences regarding the type of surgery, age, time of marriage, education level, occupation, chemotherapy, use of Tamoxifen, and radiotherapy in the sexual activities of premenopausal women with breast cancer. However, quality-related information utilizing qualitative in-depth interviews, revealed 3 issues regarding sexual behaviors.. Participants reported physical discomfort such as vaginal dryness, dyspareunia, emotional changes such as decrease in sexual confidence, and interaction-related changes such as mandatory sexual life, sexual intimacy with one's partner, and being more active sexual behaviors. CONCLUSION: There were complex changes associated with sexual behavior after surgery for women with breast cancer which included various events related to stress regarding sexual behavior. Communication between women with breast cancer, their partners, and medical caregivers has a ability to maximize the sense of sexual wellbeing while minimizing the sexual crises.